2016
DOI: 10.1007/s13277-015-4676-4
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-transferase M1 null genotype related to poor prognosis of colorectal cancer

Abstract: Published studies showed controversial findings about the relationship between glutathione S-transferase M1 (GSTM1) null genotype and clinical outcomes of patients with colorectal cancer. We performed a meta-analysis to quantitatively assess the association between GSTM1 null genotype and prognosis of patients with colorectal cancer. We systematically searched Pubmed, Embase, and Web of Science to identify prospective or retrospective cohort studies assessing the association of GSTM1 null genotype with overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…It is a multifactorial disease involving factors of genetics, environmental, and lifestyle. Accumulated evidence has documented several risk factors associated with the development of CRC, including physical inactivity, alcohol, smoking, and red and processed meat consumption . Additionally, some kinds of diseases have been demonstrated to be related to increased risk of CRC, such as type 2 diabetes mellitus, obesity, and inflammatory bowel diseases .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a multifactorial disease involving factors of genetics, environmental, and lifestyle. Accumulated evidence has documented several risk factors associated with the development of CRC, including physical inactivity, alcohol, smoking, and red and processed meat consumption . Additionally, some kinds of diseases have been demonstrated to be related to increased risk of CRC, such as type 2 diabetes mellitus, obesity, and inflammatory bowel diseases .…”
Section: Introductionmentioning
confidence: 99%
“…Accumulated evidence has documented several risk factors associated with the development of CRC, including physical inactivity, alcohol, smoking, and red and processed meat consumption. 2,3 Additionally, some kinds of diseases have been demonstrated to be related to increased risk of CRC, such as type 2 diabetes mellitus, obesity, and inflammatory bowel diseases. [4][5][6] Increasing number of studies have implicated that non-coding RNAs play critical roles in the initiation and progression of CRC, many of which may even affect the prognosis of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown the evidence that alcohol, smoking, lifestyle, and genetic predisposition are associated with increased risk of CRC. [11][12][13] Despite great progress in the early diagnosis and treatment of this deadly disease, searching for more sensitive and specific biomarkers for CRC is urgent for improving the quality of life and patients' prognosis. Recently, circulating exosome-encapsulated miRNAs have been demonstrated to play crucial roles in colorectal carcinogenesis and even the prognosis of patients with CRC.…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of this disease is not fully understood up to date. Many studies have shown the evidence that alcohol, smoking, lifestyle, and genetic predisposition are associated with increased risk of CRC . Despite great progress in the early diagnosis and treatment of this deadly disease, searching for more sensitive and specific biomarkers for CRC is urgent for improving the quality of life and patients’ prognosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation